Verse. Book two, The second gate - Beck, Sam (Freelance artist) (Verse, 2022)
"The battle for the future of magic has taken its first prisoner. Held captive by the leaders of a dangerous new movement, Neitya is forced to face a darker side of her abilities that threatens to tear her away from Fife, her only true friend. The only way back to one another may be to follow their destinies down divergent paths and discover what it means to face their worst fears alone."--Back cover